Biomass measurement by flow cytometry during solid‐state fermentation of basidiomycetes. (4th December 2014) - Steudler, Susanne; Böhmer, Ulrike; Weber, Jost; Bley, Thomas
Abstract Solid‐state fermentation (SSF) is a robust process that is well suited to the on‐site cultivation of basidiomycetes that produce enzymes for the treatment of lignocellulosics. Reliable methods for biomass quantification are essential for the analysis of fungal growth kinetics. However, direct biomass determination is not possible during SSF because the fungi grow into the substrate and use it as a nutrient source. This necessitates the use of indirect methods that are either very laborious and time consuming or can only provide biomass measurements during certain growth periods. Here, we describe the development and optimization of a new rapid method for fungal biomass determination during SSF that is based on counting fungal nuclei by flow cytometry. Fungal biomass was grown on an organic substrate and its concentration was measured by isolating the nuclei from the fungal hyphae after cell disruption, staining them with SYTOX® Green, and then counting them using a flow cytometer. A calibration curve relating the dry biomass of the samples to their concentrations of nuclei was established. Multiple buffers and disruption methods were tested. The results obtained were compared with values determined using the method of ergosterol determination, a classical technique for fungal biomass measurement during SSF. Our new approach can be used to measure fungal biomass on a range of different scales, from 15 mL cultures to a laboratory reactor with a working volume of 10 L (developed by the Research Center for Medical Technology and Biotechnology (fzmb GmbH)). © 2014 International Society for Advancement of Cytometry